Implementasi Etnomatematika Berbasis Alat Kesenian Rebana untuk Memfasilitasi Kemampuan Matematis Siswa: Systematic Literature Review - Nisa', Isna Luthfi Atin; Malasari, Putri Nur (Square : Journal of Mathematics and Mathematics Education, 2024)
Ethnomathematics serves as a bridge connecting culture, education, and mathematics. It involves leveraging cultural artifacts and practices to enhance mathematical understanding. The concept of ability refers to an individual's capacity to perform tasks effectively in various contexts. Numerous studies have explored the implementation of cultural artifacts, such as reed art tools, to support students' mathematical skills. However, questions remain regarding the validity of these tools in facilitating mathematical competence. This study aims to evaluate students' mathematical abilities by examining the application of ethnomathematical principles in the context of tambourine art as a cultural and artistic instrument. A Systematic Literature Review (SLR) methodology was employed, with data collected from nine journal articles retrieved from Google Scholar. The findings indicate that ethnomathematical approaches using tambourine art are effective in enhancing students' mathematical abilities, particularly at the elementary and junior high school levels.Keywords: ethnomathematics, tambourine, mathematical ability.